Immunological Testing in Assisted Reproductive Technology - Odendaal, Joshua; Quenby, Siobhan (Seminars in Reproductive Medicine, 2021)
Fetal implantation requires carefully orchestrated involvement of the maternal immune system. Aberrant function within implantation has been suggested as a cause of implantation failure. The emergence of immunological theories of miscarriage has led to immunological testing as an adjuvant treatment in assisted reproductive technology; however, it remains controversial, with mixed evidence both for immunological cause and the benefits of immunological testing. Literature on common methods of immunological testing within assisted reproductive technology is reviewed including those of peripheral and uterine natural killer cells, chronic endometritis, and T-helper cells cytokine ratio. There is little consensus in the evidence on immunological testing in the context of recurrent implantation failure. The field is limited by a lack of uniformity in approach to testing and heterogeneity of the pathophysiological cause. Nevertheless, the maternal immune system is heavily involved in implantation and the new era of personalized medicine ensures that a more defined approach to immunological testing will be achieved.
Keywords: assisted reproductive technology; recurrent implantation failure; immunological testing; natural killer cells; chronic endometritis